2021
DOI: 10.33024/jpm.v3i1.3316
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Deskriptif Quarter-Life Crisis Pada Lulusan Perguruan Tinggi Universitas Katolik Musi Charitas

Abstract: QUARTER-LIFE CRISIS DESCRIPTVE ANALYSIS ON COLLEGE GRADUATES OF KATOLIK MUSI CHARITAS UNIVERSITY Quarter-life crisis is a phenomenon of anxiety over the age of 20, which is the transition from late adolescence to adulthood. The research objective was to reveal the quarter-life crisis phenomenon in freshmen graduates. Research participants were 115 graduate students for the 2019 and 2020 periods from the  Catholic University of Musi Charitas. The analysis technique used is statistical description analysis, data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…According to the results of research by (Riyanto and Arini 2021), entitled "Descriptive analysis of quarter life crisis in college graduates from the Musi Charitas Catholic University," most of the respondents who have just finished college are worried about work problems. Based on the results of the research interview, it was concluded that students who had just graduated and had not yet worked experienced the early stages of a quarter life crisis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of research by (Riyanto and Arini 2021), entitled "Descriptive analysis of quarter life crisis in college graduates from the Musi Charitas Catholic University," most of the respondents who have just finished college are worried about work problems. Based on the results of the research interview, it was concluded that students who had just graduated and had not yet worked experienced the early stages of a quarter life crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan data dari PDSKJI (Perhimpunan Dokter Spesialis Kedokteran Jiwa Indonesia, 2021) pemikiran bunuh diri paling banyak dilakukan oleh penduduk usia produktif. Penelitian yang dilakukan oleh (Riyanto & Arini, 2021) menyatakan bahwa 86% fresh graduate mengalami quarter life crisis yang pada umumnya disebabkan oleh kekhawatiran akan sulitnya mendapat pekerjaan, kecemasan tentang masa depan dan ketidaknyamanan realitas dunia kerja dengan apa yang dibayangkan. Rahmania FA & Tasaufi (2020) mengungkapkan bahwa mahasiswa pasca wisuda atau fresh graduate mengalami kebingungan tentang apa yang harus dipilih untuk masa depannya dan tuntutan dari lingkungannya mengindikasi terjadinya quarter life crisis.…”
Section: Pendahuluanunclassified
“…Lansia sangat rentang terhadap depresi terhadap kondisinya, salah satu kegiatan yang mudah dilakukan dalam memebrikan intrevensi untuk menurunkan nyeri sendi dengan adanya senam, senam sendiri merupakan gerakan ringan yang dapat dilakukan dan dengan mudah di modifikasi sesuai dengan pesertanya, salah satu senam yang digunakan untuk mengurangi rasa nyeri sendi adalah senam rematik yang dilakukan secara teratur dan kontinyu (Windahandayani et al, 2022). Senam rematik merupakan latihan gerak untuk mencegah dan memebrikan efek terapi terhadap gejala penyakit rematik, adapun manfaat senam rematik menurunkan nyeri kronik rematoid atritis dengan cara meningkatkan kelenturan dan rentang gerak sendi, jika otot sendi lebih rileks, kekakuan dan nyeri sendi daat berkurang (Pranata, 2020).…”
Section: Pendahuluanunclassified